Kinetics of the Inhibition of Tissue Factor-Factor Vila by Tissue Factor Pathway Inhibitor - Lindhout, Theo; Franssen, Jo; Willems, George (Thrombosis and Haemostasis, 1995)
Tissue factor-factor VIIa catalysed activation of factor X and factor IX is inhibited by the complex of tissue factor pathway inhibitor (TFPI) and factor Xa. At present, no information is available as to what extent the kinetics of complex formation between TFPI and factor Xa during factor X activation contribute to the overall rate of inactivation of the factor X converting complex. We have determined the kinetic parameters of the individual reactions, i. e. factor X activation, formation of the TFPI-factor Xa complex, and inactivation of tissue factor-factor VIIa by the TFPI-factor Xa complex. We modelled the overall reaction by assuming a two-step reaction: factor Xa generated by tissue factor-factor VIIa forms a reversible complex with TFPI and in the second step this complex forms a reversible quaternary complex with tissue factor- factor VIIa. The validity of the model was demonstrated by analysis of factor Xa generation curves in the presence of TFPI. Independently determined constants for factor X activation (kcat= 12 s-1, Km = 70 nM) and inhibition of tissue factor-factor VIIa by TFPI-factor Xa complex (rate constant of inhibition of 1.1 × 108 M-1s-1) were used. The association rate constant of the formation of the TFPI-factor Xa complex was estimated by fitting the model to the data. The rate constants of association of the complex between factor Xa and the variants full length TFPI, TFPI 1-247 and TFPI1-61 were very close to the values determined independently in a kinetic study on the inhibition of factor Xa in the presence of phospholipids, namely 3.4 × 106 M-1s-1, 0.4 × 106 M-1s-1 and 0.3 × 106 M-1s-1, respectively. These results indicate that the factor Xa-dependent inhibition of tissue factor-factor VIIa-catalysed factor X activation by TFPI can be adequately described by the two-step reaction sequence. We found that phospholipids (25 mol % phosphat-idylserine/75 mol % phospatidylcholine) increased the rate constant of association with factor Xa for full length TFPI, but not for the C-ter- minus truncated TFPI. Our results further indicate that optimal inhibition of tissue factor-factor VIIa activity is obtained with full length TFPI because of the higher rate of TFPI-factor Xa complex formation.